KESIAPAN DALAM MENGHADAPI ERA PERDAGANGAN BEBAS MASYARAKAT EKONOMI ASEAN (MEA) - Aan Zulyanto (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2016)
Abstract: The commitment of ASEAN countries to achieve a single economic zone, the ASEAN Economic Community (AEC), applies effectively in early 2016. The Economic Integration is expected will enhance the traffic of goods, services and production factors between ASEAN countries due to the elimination of tariff and regulation. For Indonesia, the ASEAN region has enough contribute to the national economy because more than 20 percent of the activities carried out Intra ASEAN trade. Nevertheless, there are still some issues that need more attention to get gain from the free trade. (i) Trade deficit in Intra-ASEAN continues to increase. Indonesia gets only a trade surplus in four countries; Philippines, Myanmar, Cambodia, and Laos, while the other five ASEAN countries, Indonesia has a large deficit. Unlucky, the surplus comes from small value of transactions, while the deficit occurred in countries with large trade transactions. (ii) The Indonesia competitiveness in ASEAN is relatively still low. The quality of infrastructure, institutional, technological readiness and labor market efficiency is relatively underdeveloped compared with other countries. Nonetheless, the government has been working to increase competitiveness through standardization system and accelerating the development of policies through MP3EI. Keywords: International Trade, Competitiveness, ASEAN Economic Community (AEC)